Association between esophageal cancer in middle-aged and elderly patients and body mass index and waist-to-hip ratio. Issue 3 (1st September 2014) - Yan, Lihui; Shan, Zhongyuan; Sun, Ying; Yan, Ying; Lu, Zhiquan
Abstract : Objective: This study determined the relationship between esophageal cancer in middle-aged and elderly patients and body mass index (BMI) and waist-to-hip ratio (WHR). Methods: A hospital-based case-control study was adopted. Two hundred eighty-two patients who were diagnosed with esophageal cancer through clinical endoscopy, X-ray examination, or histopathologic evaluation, and underwent surgery or received chemotherapy were enrolled as cases. The control group consisted of 282 patients without any cancers or esophageal diseases who were hospitalized during the same period in the same hospital. Face-to-face interviews were conducted using standard survey forms, and the height, weight, waist circumference, and hip circumference were measured to calculate the BMI and WHR. The odds ratio (OR) and 95% confidence interval (CI) between the patient BMI and WHR and esophageal cancer were estimated using a multi-factor logistic regression model. Results: There was no statistical difference between the case and control groups with respect to age, gender, occupation, educational background, place of residence, and history of high blood pressure ( P >0.05); however, there were more cases who smoked cigarettes and consumed alcohol than controls ( P <0.05). Single-factor logistic regression analysis showed that the risk for esophageal cancer in overweight and obese patients was 1.53- and 1.82-fold that of normoweight patients, respectively. The risk for esophageal cancer in patients with a WHR in the highest quartile was 1.85-fold the control patients with a WHR in the lowest quartile. After confounding factors, such as gender and age, were adjusted, multi-factor logistic regression analysis indicated that the risk for esophageal cancer in overweight and obese patients increased by 59.4% (OR=1.594) and 78.2% (OR=1.782), respectively, when compared with normoweight patients. Conclusion: BMI and WHR are important risk factors for esophageal cancer. Overweight and obese patients are at increased risk for esophageal cancer. Maintaining a normal weight may be a factor in preventing esophageal cancer.